The Production of Flexible Attitudes in the Canadian Pulp and Paper Industry - Smith, Michael (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1999)
It is widely beleived that both economic security and management policies that foster employee trust increase the willingness of employees to be flexible with respect to work practices and to accept economic policies that foster competition in product markets. These claims, however, rest either on fairly indirect evidence — an apparent association between the presence in countries of institutions that provide economic security and betterperformance on one or another macroeconomic indicator— or on a series of generally sketchy case studies. In this article relevant data are analyzed from a representative sample of pulp and paper industry employees in Canada. The results provide only weak support for claims with respect to the effects of employment security and trust, thus suggesting some modifications to the standard interpretation.